INTERPRETASI MAKNA PADA WARUNG KOPI ACEH Studi Kasus: Warung Kopi Solong di Banda Aceh - Riza Aulia Putra; Agus S. Ekomadyo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title: The Interpretation of Meaning in Aceh Coffee Shop The gathering tradition in Acehnese people for silaturrahmi has long been established. A coffee shop is one of the artefacts from Aceh traditions or gathering culture for Acehnese people. Coffee shop is a place for social interaction and other various activities. One example of case that was taken is Solong Coffee shop located in the city of Banda Aceh. The purpose of this paper is to explore the spirit or genius loci that makes coffee shop in Aceh continue to live and thrive. By using the thinking of Norberg-Schulz, it will be studied and explored for more about image, space and character that create the genius loci in a Aceh coffee shop to attract the Acehnese people to choose the coffee shop as a place to do their various activities and social interaction. Reviewing these elements will obtain many factors that affect a place such as the meaning, identity and history of the place.